High-intensity interval training shock microcycle for enhancing sport performance: A brief review - Dolci, F.; Kilding, A. E.; Chivers, P.; Piggott, B.; Hart, N. H. (The Journal of Strength and Conditioning Research, 2020)
High-intensity interval training (HIIT) is a powerful strategy to develop athletes' fitness and enhance endurance performance. Traditional HIIT interventions involve multiple microcycles (7-10 days long) of 2-3 HIIT sessions each, which have been commonly supported to improve athletic performance after a minimum period of 6 weeks training. Regardless of the efficacy of such an approach, in recent years, a higher frequency of HIIT sessions within a unique microcycle, commonly referred to as an HIIT shock microcycle, has been proposed as an alternative HIIT periodization strategy to induce greater and more efficient endurance adaptation in athletes. This review article provides an insight into this new HIIT periodization strategy by discussing (1) HIIT shock microcycle format and design; (2) the sustainability of this training strategy; (3) effects on performance and physiological parameters of endurance; and (4) potential mechanisms for improvements. Evidence advocates the sustainability and effectiveness of HIIT shock microcycle in different athletes to improve intermittent and continuous running/cycling performance and suggests mitochondria biogenesis as the main acute physiological adaptation following this intervention.